Pengaruh Leverage, Net Working Capital, Capital Expenditure dan Liquidity terhadap Cash Holding pada Perusahaan Sektor Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024 - Stella Stella; Henryanto Wijaya (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The management of cash reserves represents a vital component of corporate financial administration, essential for sustaining liquidity and ensuring operational continuity. The magnitude of cash holdings is shaped by a variety of internal determinants, including leverage, net working capital, capital expenditures, and liquidity levels. Nevertheless, previous research has yielded divergent results, underscoring the necessity for additional investigation, especially within the property and real estate sectors. This inquiry adopts a quantitative methodology characterized by an explanatory research design. Secondary data were sourced from the financial statements of property and real estate enterprises listed on the Indonesia Stock Exchange for the time frame of 2021 to 2024. Through purposive sampling, a total of 36 firms were identified, culminating in 136 observations. The data were subjected to analysis via panel regression utilizing the Random Effect Model. The results reveal that net working capital exerts a positive and statistically significant influence on cash holdings. Conversely, leverage, capital expenditures, and liquidity do not manifest a significant impact on cash reserves. Collectively, all independent variables exert a significant influence on cash holdings. This study concludes that net working capital serves as the principal determinant of cash holdings in property and real estate firms. The other variables do not exhibit significant effects when considered in isolation. It is advisable for future research to incorporate additional variables such as profitability and firm size to enhance the explanatory capacity of the analytical model.